Analisa JST Untuk Memprediksi Pembuatan SIM Menggunakan Metode Algoritma Backpropagation - Rahul, Mirza; Gunawan, Indra; Anggraini, Fitri; Sumarno, Sumarno; Kirana, Ika Okta (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
In a service company there are customers who become consumers of the company. Customer satisfaction is formed from the level of performance and company loyalty. If the company does not know about the level of customer satisfaction, the company also cannot develop their services. So from that Pematangsiantar Police Satpas need to know the level of customer satisfaction in order to improve their performance and loyalty. So research is needed to determine the level of customer satisfaction through the Artificial Neural Network method with the backpropagation algorithm which is then predicted and the best results will be searched to be used to give the best results and will display the results of the problems encountered.